Status organizacyjny nierzymskokatolickich związków wyznaniowych prawnie uznanych w II Rzeczypospolitej Polskiej - Baszak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The author presents the organizational status of non-Roman Catholic religious unions legally recognized in the Second Republic, i.e., the Jewish Religious Union, the Eastern Old Believers’ Church with no clerical hierarchy, the Muslim Religious Union, the Karaite Religious Union, the Evangelical-Augsburg Church and the Polish Autocephalous Orthodox Church. The article shows that the organizational status of these unions resulted directly from the acts regulating their legal status, and the characteristic feature was that the clear line between the internal system and external relations with the state was blurred. In addition, the author points out that the organizational status of non-Roman Catholic religious unions legally recognized, was influenced by the denominational and nationality policy pursued by the state authorities towards individual unions and the attitude of religious minorities towards the Polish state.
Keywords: religious law in the Second Republic; codification of religious law; religious unions of religious minorities in the Second Republic; non-Roman Catholic religious unions legally recognized in the Second Republic; the Constitution of the Republic of Poland of March 17, 1921